A Cobalt(II) Complex Bearing the Amine(imine)diphosphine PN(H)NP Ligand for Asymmetric Transfer Hydrogenation of Ketones. Issue 1 (20th October 2020) - Huo, Shangfei; Chen, Hong; Zuo, Weiwei
Abstract : Novel chiral cobalt complex a containing amine(imine)diphosphine PN(H)NP ligand and complex b containing bis(amine)diphosphine PN(H)N(H)P ligand were synthesized. The structures of two complexes were characterized by X‐ray crystallography and high resolution mass spectrometry. The catalytic performances of cobalt complexes a and b for asymmetric transfer hydrogenation (ATH) of ketones under mild conditions were evaluated using 2‐propanolisopropanol as solvent and hydrogen source after being activated by 8 equivalents of base. Complex a showed a good reactivity for reduction of ketones, with a turnover number (TON) of up to 555, and a maximum enantiomeric excess ( ee ) value of up to 91 %. Complex b exhibited inertness for hydrogenation of ketones. Electronic structure studies on a and b were conducted to account for the function of ligands on the catalytic performances. Abstract : The cobalt complex bearing amine(imine)diphosphine PN(H)NP ligand could prompt asymmetric transfer hydrogenation of wide range of ketones under very mild conditions after activated by base. The amido‐ene(imido) group in the real catalyst is a key factor to enable its catalytic performance.